Flipbook Records the Journey of Creating Gamelan Kaca by Thoni Konde and the Muria Raya Festival Community - Nadi, Chici Yuliana; Komariah, Arfiati Nurul (TEXTURE Art and Culture Journal, 2025)
Muhammad Sulthoni or often called Thoni Konde, is an artist who creates glass gamelan works who lives in the city of Solo. The glass gamelan he created was made from waste glass materials found around him. Konde together with people in several cities make and play the glass gamelan on various occasions. Not only creating glass gamelan, Konde aspires to create a glass gamelan festival which will feature glass gamelan performances from the communities he supports. The Muria Raya Festival Foundation (FMR) through the FMR #4 collaborated with Konde and the Muria community together to create "Gatotkaca" (Total Glass Gamelan), a gamelan made entirely of glass, which was then exhibited and played at the peak of the event FMR #4. The author then recorded this innovative and monumental activity in a digital flipbook which compactly and comprehensively displays photos and videos of the track record of Gatotkaca's creation journey which can be accessed via the website page. It is hoped that this creation will be a trigger for Konde and FMR to continue organizing documentation data digitally so that in the future it can be used as a media for promotion and representation of oneself and the organization. In creating this digital flipbook, the Alessi and Trollip model development research method was used which was modified according to research needs, through stages (1) planning; (2) design; and (3) development. Field studies are carried out through documentation, interviews and observations.